PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA N 1 KEPENUHAN KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - -, Jonwandri; Afifah, Nurul; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The study aims to determine the effect of the learning model TGT Biology student learning outcomes in viralmaterial class X SMA N 1 Kepenuhan Rokan Hulu Learning Year 2014/2015. This type of research is QuasiExperiment. The study population was a whole class X SMA N 1 Kepenuhan. Samples were class XA(Experimental) and XB (Control) SMA N 1 Kepenuhan. Data collection techniques using a multiple-choice test.The data analysis technique is a test "t". The results showed there are significant learning model TGT onlearning outcomes Biology class X SMA N 1 Kepenuhan Year 2014/2015 Learning